WIMAX TESTBED - KOH , MINGHAO (Universiti Teknologi Petronas, 2008)
WiMAX, the Worldwide Interoperability for Microwave Access, is a telecommunications technology aimed at providing wireless data over long distances in a variety of ways, from point-to-point links to full mobile cellular type access. It is based on the IEEE 802.16 standard, which is also called Wire IessMAN. The name WiMAX was created by the WiMAX Forum, which was formed in June 2001 to promote conformance and interoperability of the standard. The forum describes WiMAX as a standards-based technology enabling the delivery of last mile wireless broadband access as an alternative to cable and DSL. This Final Year Project attempts to simulate via Simulink, the working mechanism of a WiMAX testbed that includes a transmitter, channel and receiver. This undertaking will involve the baseband physical radio link. Rayleigh channel model together with frequency and timing offsets are introduced to the system and a blind receiver will attempt to correct these offsets and provide channel equalization. The testbed will use the Double Sliding Window for timing offset synchronization and the Schmid! & Cox algorithm for Fractional Frequency Offset estimation. The Integer Frequency Offset synchronization is achieved via correlation of the incoming preamble with its local copy whereas Residual Carrier Fr~quency Offset is estimated using the L th extension method. A linear Channel Estimator is added and combined with all the other blocks to form the testbed. From the results, this testbed matches the standard requirements for the BER when SNR is 18dB or higher. At these SNRs, the receiver side of the testbed is successful in performing the required synchronization and obtaining the same data sent. Sending data with SNR lower than 18dB compromises its performance as the channel equalizer is non-linear. This project also takes the first few steps of hardware implementation by using Real Time Workshop to convert the Simulink model into C codes which run outside MATLAB. In addition, the Double Sliding Window and Schmid! & Cox blocks are converted to Xilinx blocks and proven to be working like their Simulink counterparts.